2010
DOI: 10.1038/nrn2889
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases of the non-conscious perception of emotional signals

Abstract: | Many emotional stimuli are processed without being consciously perceived. Recent evidence indicates that subcortical structures have a substantial role in this processing. These structures are part of a phylogenetically ancient pathway that has specific functional properties and that interacts with cortical processes. There is now increasing evidence that non-consciously perceived emotional stimuli induce distinct neurophysiological changes and influence behaviour towards the consciously perceived world. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
780
8
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 892 publications
(859 citation statements)
references
References 162 publications
(147 reference statements)
39
780
8
3
Order By: Relevance
“…Under the assumption that the special role of faces is not fixed by their physical properties but by their functional ones, the findings reported above converge with the idea that nonconscious emotion processing in blindsight is not specific for faces, but rather for biologically primitive emotional expressions that are clearly associated with action tendencies and to which we are evolutionary prepared to respond (Tamietto & de Gelder, 2010).…”
Section: When Affective Blindsight Obtains When It Fails and Whysupporting
confidence: 64%
See 2 more Smart Citations
“…Under the assumption that the special role of faces is not fixed by their physical properties but by their functional ones, the findings reported above converge with the idea that nonconscious emotion processing in blindsight is not specific for faces, but rather for biologically primitive emotional expressions that are clearly associated with action tendencies and to which we are evolutionary prepared to respond (Tamietto & de Gelder, 2010).…”
Section: When Affective Blindsight Obtains When It Fails and Whysupporting
confidence: 64%
“…Contemporary neuroscience is replete with examples of social and affective processes that occur without or outside conscious experience (de Gelder, de Haan, & Heywood, 2001; de Gelder, Hortensius, & Tamietto, 2012;Tamietto & de Gelder, 2010;Vuilleumier, 2005). This evidence has contributed significantly to the burgeoning field of social and affective neuroscience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, showing that the ability to discriminate graded intensities of angry faces was positively correlated with the ability to discriminate unperfect/perfect circles (radial frequency patterns), Marneweck and Hammon indicated that impaired ability to perceive visual forms could contribute to FER deficit in PD 38. It is noteworthy that visual and emotional systems are extensively interconnected; for example, the amygdala is connected to the superior colliculus via the pulvinar, to the OFC, and the anterior cingulate cortex, as well as to cortical visual regions in the temporal cortex 41. Furthermore, the idea that FER deficit in PD could be secondary to executive dysfunction is an old one.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…Like Gray and Tickle‐Degnen,12 we noted that FER deficit in PD affected all the basic emotions but was greater for negative emotions (64% of studies highlighted a global deficit, 44% for anger, 27% for happiness; Table 1). This could echo the subcortical pathway involving the pulvinar, the amygdala, and the striatum, which may lead to a coarse but fast visual information processing 40, 41. Indeed, because of its evolutionary relevance, this preserved route may induce a preattentive and autonomic bias toward threatening stimuli like angry faces 42, 43.…”
Section: Facial Emotion Recognition In Pdmentioning
confidence: 99%